An Evaluation of Rural Electrification and Households’ Poverty in Ikole Local Government Area, Ekiti State, Nigeria: An FGT Approach - Osanyinlusi, Oladele I.; Awotide, Bola A.; Awoyemi, Taiwo T.; Ogunniyi, Adebayo I.; Ogundipe, Adeyemi A. (International Journal of Energy Economics and Policy, 2017)
The rural areas in Nigeria have witnessed intense neglect and inadequate rural infrastructural development. This is contrary to the backdrop experienced in emerging cities where the provision of rural infrastructure was critical for improving the quality of rural life and opening up the areas for development. This study evaluated the relevance of rural electrification on households’ poverty using structured questionnaire and a multistage sampling procedure to obtain cross sectional data. A total of 114 rural households were randomly selected, out of which 60 had access to electricity and 54 did not. The Foster-Greer-Thorbecke technique was used to evaluate the poverty incidence among the households. The results revealed that the mean age of the respondents was 52years. The mean household size and farm size was 8 and 28.9 percent of the respondents had no formal education with majority engaging in farming as main occupation. The households in electrified communities spent more averagely, N4,017.90/Month on the alternative sources of energy than their counterpart in non-electrified communities who averagely spent N2,890.90/Month. The results further revealed that households in non-electrified communities were poorer than their counterpart in electrified communities. Therefore, rural electrification can actually curb poverty and improve standard of living in rural Nigerian areas. Keywords: Electrification, Households, Infrastructure, Poverty, Rural Nigeria JEL Classifications: I32, O18, R2